Licensing of Land of State as Soyness of Agricultural and Land Function at Semarang Regency - Santoso, Budi (Faculty of Law, Universitas Negeri Semarang, 2022)
Licensing and optimization are regulated in Government Regulation No. 27 of 2014 on the management of state / regional property. Licensing is one of the most important aspects of land management for the legality of tenure, one of the productive activities in it is to make it an agricultural land. Unfortunately, in order to obtain licensing rights to agriculture is difficult to get, one example of the case that occurred is in the area of ​​ungaran Semarang regency. The difficulty of obtaining such permits can certainly lead to unoptimal use of unoccupied vacant land. In addition, the difficulty of licensing for agriculture will cause many losses for both the government and the farmers, such as the unoptimal agricultural activities of the area to be vulnerable to shift the land into non-agricultural functions, it is feared that farmers will be reluctant to bureaucratize the government. This study is expected to contribute to the increasing rules of use and management of deadly state property in the future.